2009
DOI: 10.1099/vir.0.004754-0
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of the biological and biochemical characteristics of bovine spongiform encephalopathy prions during interspecies transmission in transgenic mice models

Abstract: In the interspecies transmission of prions, the species barrier influences the susceptibility of the host. Bovine spongiform encephalopathy (BSE) prions affect a wide range of host species but do not affect hamsters. In order to study this species barrier, this study analysed the transmissibility of BSE prions to several lines of transgenic (Tg) mice, including those expressing mouse and hamster chimeric prion proteins (MH2M and MHM2 mice). BSE prions were transmitted to tga20, MHM2 and ICR mice, and the incub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
22
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 35 publications
2
22
0
Order By: Relevance
“…However, the latter difference may be due to the lack of PrP C expression by Purkinje cells in this transgenic mouse strain (7,27). The differences in neuropathological features between CWD-infected voles and Tg(CerPrP)1536 mice are consistent with the alterations in strain properties sometimes observed upon transspecies passage of CWD and other TSEs (26,35,39).…”
Section: Discussionsupporting
confidence: 71%
“…However, the latter difference may be due to the lack of PrP C expression by Purkinje cells in this transgenic mouse strain (7,27). The differences in neuropathological features between CWD-infected voles and Tg(CerPrP)1536 mice are consistent with the alterations in strain properties sometimes observed upon transspecies passage of CWD and other TSEs (26,35,39).…”
Section: Discussionsupporting
confidence: 71%
“…The lack of transmissibility of the classical BSE agent from cattle to hamsters and its efficient transmission after a first passage in C57BL/6 wild-type mice are consistent with the results of previous studies (11,20,21). Hamsters were also susceptible to the SSBP/1 isolate from ovine transgenic TgOvPrP4 mice, consistent with the known susceptibility of hamsters to some scrapie sources (14).…”
supporting
confidence: 80%
“…The initial isolation of two biologically different prion strains, associated with distinct PrP properties, in transmissible mink encephalopathy (TME) was first achieved in hamsters (5). Surprisingly, bioassay studies in hamsters after challenge with the C-type BSE agent from cattle showed that it was inefficient (11,21). This was attributed to the existence of a so-called "species barrier," a concept based on the observation that the transmission of prion diseases between different species is typically far less efficient than within species (10).…”
mentioning
confidence: 99%
“…However, the conclusion that transgenic mice overexpressing PrP C lead to a considerable reduction of the incubation time is also a point still open to debate: indeed, while this is true for a number of mouse and hamster strains, this statement seems not to be true in all cases. As an example, the incubation time of BSE in tg mice which over-express mouse PrP (tga20) is similar if not longer than in wild type mice (Yokoyama et al, 2009). …”
Section: Successful Amplification Of Prpmentioning
confidence: 99%